Culture conditions have an impact on the maturation of traceable, transplantable mouse embryonic stem cell‐derived otic progenitor cells. (21st April 2016) - Abboud, Nesrine; Fontbonne, Arnaud; Watabe, Isabelle; Tonetto, Alain; Brezun, Jean Michel; Feron, François; Zine, Azel
Abstract: The generation of replacement inner ear hair cells (HCs) remains a challenge and stem cell therapy holds the potential for developing therapeutic solutions to hearing and balance disorders. Recent developments have made significant strides in producing mouse otic progenitors using cell culture techniques to initiate HC differentiation. However, no consensus has been reached as to efficiency and therefore current methods remain unsatisfactory. In order to address these issues, we compare the generation of otic and HC progenitors from embryonic stem (ES) cells in two cell culture systems: suspension vs. adherent conditions. In the present study, an ES cell line derived from an Atoh1 ‐green fluorescent protein (GFP) transgenic mouse was used to track the generation of otic progenitors, initial HCs and to compare these two differentiation systems. We used a two‐step short‐term differentiation method involving an induction period of 5 days during which ES cells were cultured in the presence of Wnt/transforming growth factor TGF‐β inhibitors and insulin‐like growth factor IGF‐1 to suppress mesoderm and reinforce presumptive ectoderm and otic lineages. The generated embryoid bodies were then differentiated in medium containing basic fibroblast growth factor (bFGF) for an additional 5 days using either suspension or adherent culture methods. Upon completion of differentiation, quantitative polymerase chain reaction analysis and immunostaining monitored the expression of otic/HC progenitor lineage markers. The results indicate that cells differentiated in suspension cultures produced cells expressing otic progenitor/HC markers at a higher efficiency compared with the production of these cell types within adherent cultures. Furthermore, we demonstrated that a fraction of these cells can incorporate into ototoxin‐injured mouse postnatal cochlea explants and express MYO7A after transplantation. Copyright © 2016 John Wiley & Sons, Ltd.